Education and occupational social class: which is the more important indicator of mortality risk?. Issue 3 (March 1998) - Davey Smith, G; Hart, C; Hole, D; MacKinnon, P; Gillis, C; Watt, G; Blane, D; Hawthorne, V
Abstract : STUDY OBJECTIVES: In the UK, studies of socioeconomic differentials in mortality have generally relied upon occupational social class as the index of socioeconomic position, while in the US, measures based upon education have been widely used. These two measures have different characteristics; for example, social class can change throughout adult life, while education is unlikely to alter after early adulthood. Therefore different interpretations can be given to the mortality differentials that are seen. The objective of this analysis is to demonstrate the profile of mortality differentials, and the factors underlying these differentials, which are associated with the two socioeconomic measures. DESIGN: Prospective observational study. SETTING: 27 work places in the west of Scotland. PARTICIPANTS: 5749 men aged 35-64 who completed questionnaires and were examined between 1970 and 1973. FINDINGS: At baseline, similar gradients between socioeconomic position and blood pressure, height, lung function, and smoking behaviour were seen, regardless of whether the education or social class measure was used. Manual social class and early termination of full time education were associated with higher blood pressure, shorter height, poorer lung function, and a higher prevalence of smoking. Within education strata, the graded association between smoking and social class remains strong, whereas within social class groups the relation between education and smoking is attenuated. Over 21 years of follow up, 1639 of the men died. Mortality from all causes and from three broad cause of death groups (cardiovascular disease, malignant disease, and other causes) showed similar associations with social class and education. For all cause of death groups, men in manual social classes and men who terminated full time education at an early age had higher death rates. Cardiovascular disease was the cause of death group most strongly associated with education, while the non-cardiovascular non-cancer category was the cause of death group most strongly associated with adulthood social class. The graded association between social class and all cause mortality remains strong and significant within education strata, whereas within social class strata the relation between education and mortality is less clear. CONCLUSIONS: As a single indicator of socioeconomic position occupational social class in adulthood is a better discriminator of socioeconomic differentials in mortality and smoking behaviour than is education. This argues against interpretations that see cultural–rather than material–resources as being the key determinants of socioeconomic differentials in health. The stronger association of education with death from cardiovascular causes than with other causes of death may reflect the function of education as an index of socioeconomic circumstances in early life, which appear to have a particular influence on the risk of cardiovascular disease.